The recognition of the communication of signs as an inclusive right in Peru - Bermúdez Tapia, Manuel (2020)
This article proposes to evaluate the scope generated by the communication of signs as a legitimate, valid and formal communication medium, which must be recognized in favor of the deaf community throughout the Peruvian territory. In this sense, the complementarity of rights of a constitutional nature applicable to the judicial, procedural and communicative field must be evaluated in a special and humane way, since the deaf community has been attended in an equivalent way to a normal person in the process of a process judicial, generating a limiting condition because in most of the Superior Courts of Justice of the country they do not have official interpreters in this communication mechanism. The proposal to evaluate the scope of communication as a means of expression in the participation and accessibility of rights in the judicial sphere allows to detail that in the cases in which the participation of a person with hearing or oral communication limitations is registered, the participation of a person who serves as an interpreter must be considered equivalent to the provisions of subsection 19 of Article 2 of the Constitution and Article 8 of the American Convention on Human Rights.